Identity work and illness careers of patients with medically unexplained symptoms. (September 2019) - Rossen, Camilla Blach; Buus, Niels; Stenager, Elsebeth; Stenager, Egon
This article reports a case study of the illness career and identity work of patients who have had medically unexplained symptoms for many years with a particular emphasis on their interactions with a specialized and standardized health care system. Patients with medically unexplained symptoms often experience being met with mistrust and feel their identity threatened as a consequence of being illegitimately ill. There is a strong tendency in health care towards assessment thorough standardized so-called assessment packages. The study used a case study approach. Ethnographic fieldwork was carried out and several types of data were sampled through theoretical sampling, resulting in data from and about a sample of 13 patients, from which two patients were selected as cases. The study showed that a standardized health care system characterized by a tendency towards narrow diagnostic assessment with limited time can lead to a diagnostic limbo and that patients and health care professionals keep on searching for legitimate explanations for the patients' still unexplained symptoms. Consequently the patients were left in a constant identity negotiation.